The Effect of Capital Structure on Firms’ Profitability: a Case Study of Indonesian Firms - Neneng Djuaeriah; Bella Joy Winarta (Conference Series, 2020)
The purpose of this research is to seek the impact of capital structure towards firms‘ profitability on Indonesian firms listed in LQ45 using panel data of five consecutive years (2013 to 2017). The data obtained are from audited financial statements of 24 constantly listed in LQ45 . This study used the linear regression to analyze the connection between total debt to represent capital structure and firms‘ profitability of Return on Assets. This study includes growth opportunity, firm size, tangibility, liquidity and non-debt tax shield as controlled variables. The research resulted in a significant positive relationship between firms‘ profitability and capital structure. Only liquidity provides a negative significant impact on profitability. In addition to that growth opportunity and size have insignificant negative influence, while tangibility and non debt tax shields have insignificant positive influence toward profitability.